Canine Neutrophil Extracellular Traps Release Induced by the Apicomplexan Parasite Neospora caninum In Vitro - Wei, Zhengkai; Hermosilla, Carlos; Taubert, Anja; He, Xuexiu; Wang, Xiaocen; Gong, Pengtao; Li, Jianhua; Yang, Zhengtao; Zhang, Xichen (Frontiers in Immunology, 2016)
Neosporosis is considered as one of the main causes of abortion and severe economic losses in dairy industry. The Canis genus serving as one of the confirmed definitive hosts of the apicomplexan parasite Neospora caninum (N. caninum) plays a critical role in its life cycle. However, the effects of N. caninum on its definitive hosts of neutrophils extracellular traps (NETs) formation remain unclear. In the present study, N. caninum tachyzoite-induced canine NETs formation was observed by scanning electron microscopy (SEM). Visualization of DNA decorated with H3, NE and MPO within N. caninum tachyzoite-induced NETs were examined using fluorescence confocal microscopy analyses. Furthermore, the formation of canine NETs was quantified using Sytox Green staining, and the LDH levels in supernatants were examined by an LDH Cytotoxicity Assay® kit. The results clearly showed that NETs-like structures were induced by N. caninum tachyzoites, and the major components within these structures induced by N. caninum tachyzoite were further confirmed by fluorescence confocal microscopy visualization. These results suggest that N. caninum tachyzoites strongly induced NETs formation in canine PMN. In functional inhibition assays, the blockings of NADPH oxidase, NE, MPO, SOCE, ERK 1/2 and p38 MAPK signaling pathways significantly inhibited N. caninum tachyzoite-induced NETs formation, which suggests that N. caninum tachyzoite-induced NETs formation is a NADPH oxidase-, NE-, MPO-, SOCE-, ERK 1/2- and p38 MAPK-dependent cell death process. To our knowledge, this study is the first to report the formation of NETs in canine PMN against N. caninum infection.